Hemodynamic and Permeability Changes in Posterior Reversible Encephalopathy Syndrome Measured by Dynamic Susceptibility Perfusion-Weighted MR Imaging - Brubaker, Lauren M.; Smith, J. Keith; Lee, Yueh Z.; Lin, Weili; Castillo, Mauricio (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: The physiological mechanism that gives rise to posterior reversible encephalopathy syndrome (PRES) is currently unknown. We sought to better understand the mechanism of the edema formation in PRES and specifically hypothesized that this edema is caused by increased vascular permeability.METHODS: Eight consecutive patients with PRES who had been studied by using perfusion MR imaging were retrospectively identified. Perfusion images were obtained using a gradient-echo echo planar sequence with contrast enhancement. Measures of apparent diffusion coefficient (ADC), cerebral blood volume (CBV), cerebral blood flow (CBF), mean transit time (MTT) and vascular permeability (K2) were calculated in the affected posterior brain areas and normalized to values obtained in unaffected anterior brain. These values were compared with those found in healthy subjects.RESULTS: Regions of interest within the posterior affected brain indicated a significant increase in ADC values in all but one patient, a significant decrease in CBV and CBF values in all patients with PRES (average 30% of control), variable changes in MTT, and no measurable change in K2.CONCLUSION: The decrease in both CBV and CBF in PRES supports the theory of autoregulatory vasoconstriction; changes in K2 were not detected.